High-strength aluminum product and preparation method thereof
By adding rare earth oxides and carbon nanomaterials as reinforced phases to the aluminum matrix and adjusting their weight ratio and proportion, the problem of insufficient strength of traditional aluminum products is solved, significantly improving the tensile strength and yield strength of aluminum products, satisfying high Strength requirements and guarantee processing performance.
Patent Information
- Application Number
- CN202411373520.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Traditional aluminum products have shortcomings in strength and cannot meet the needs of high strength in aerospace, automobile manufacturing and mechanical engineering.
The aluminum matrix is used with rare earth oxides and carbon nanomaterials as reinforced phases. By adjusting its weight ratio and proportion, the interface combination with the aluminum alloy matrix is enhanced, which hinders crack propagation, refines grains, forms more crystal nuclei, and improves Strength of aluminum products. The specific method includes distributing the aluminum matrix and the reinforcement phase into specific ingredients, and preparing high-strength aluminum products through steps such as coarse refining, refining, degassing and slag removal and die-casting.
It significantly improves the tensile strength and yield strength of aluminum products, meets the modern industry's demand for high-strength aluminum products, and ensures good processing performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloys, and in particular to a high-strength aluminum product and a preparation method thereof. Background Art
[0002] Aluminum products are various items made of aluminum as the main material. Aluminum products are widely used because of their many advantages such as light weight, corrosion resistance, and good thermal conductivity. However, traditional aluminum products often have certain limitations in terms of strength. In many application scenarios, such as aerospace, automobile manufacturing, mechanical engineering and other fields, higher requirements are placed on the strength of aluminum products. In the field of aerospace, high-strength aluminum products can reduce the weight of aircraft while ensuring the stability and safety of the structure; in automobile manufacturing, high-strength aluminum products can improve the fuel efficiency of automobiles and enhance collision safety; in the field of mechanical engineering, high-strength aluminum products are required to withstand greater loads and complex working environments. Although the existing aluminum product preparation method can meet conventional needs to a certain extent, it is still insufficient in achieving high strength. Therefore, developing a high-strength aluminum product and its preparation method to meet the demand for high-strength aluminum products in modern industry and life has become a technical problem that needs to be solved urgently. Summary of the invention
[0003] The present invention provides a high-strength aluminum product and a preparation method thereof, which solves the problem of low strength of aluminum products in the related art.
[0004] The technical solution of the present invention is as follows: The present invention provides a high-strength aluminum product, which is composed of an aluminum matrix and a reinforcement phase. The aluminum matrix is composed of the following components by weight percentage: Mg 3%-5%, Cu 2%-4%, Mn 0.5%-1.5%, Zn1.5%-2.5%, Cr 0.01%-0.03%, Ti 0.005%-0.015%, and the balance is Al and unavoidable impurities; The reinforcing phase includes rare earth oxides and carbon nanomaterials; The weight ratio of the reinforcement phase to the aluminum product is 1-2:1000; The weight ratio of the rare earth oxide to the carbon nanomaterial is 1:1.
[0005] As a further technical solution, the rare earth oxide includes one or more of lanthanum oxide, cerium oxide, and dysprosium oxide.
[0006] As a further technical solution, the carbon nanomaterial includes one or more of carbon nanotubes, graphene, and fullerene.
[0007] As a further technical solution, when the reinforcing phase is carbon nanotubes, the carbon nanotubes are composed of single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0008] In the present invention, single-walled carbon nanotubes and multi-walled carbon nanotubes are selected as carbon nanomaterials, which can enhance the interface bonding with the aluminum alloy matrix, hinder the crack propagation, and further improve the strength of the aluminum product.
[0009] As a further technical solution, the weight ratio of the single-walled carbon nanotubes to the multi-walled carbon nanotubes is 3-4:1.
[0010] In the present invention, the ratio of single-walled carbon nanotubes to multi-walled carbon nanotubes is reasonably regulated to bring into play the synergistic enhancement effect of the two, thereby further improving the strength of the aluminum product and ensuring that the aluminum product has good processing performance.
[0011] The present invention also provides a method for preparing a high-strength aluminum product, comprising the following steps: S1, preparing materials according to the components of the aluminum matrix, performing rough refining to obtain rough-refined aluminum liquid, adding a refining and slag-removing agent to the rough-refined aluminum liquid, refining, degassing and deslagging, and obtaining an aluminum alloy melt; S2. Adding a reinforcing phase to the aluminum alloy melt, dispersing the phase evenly, and die-casting to obtain an aluminum product.
[0012] As a further technical solution, the refining slag cleaning agent is one or more of magnesium silicate, aluminum silicate, and calcium silicate.
[0013] As a further technical solution, the rough refining temperature is 700-750°C.
[0014] As a further technical solution, the temperature of the degassing and deslagging is 750-800°C and the time is 15-25 minutes.
[0015] As a further technical solution, the amount of the refining slag cleaning agent added is 0.5% to 1% of the mass of the aluminum liquid after the rough refining.
[0016] The working principle and beneficial effects of the present invention are: In the present invention, rare earth oxides and carbon nanomaterials are used as reinforcing phases, and the weight ratio of the reinforcing phases to the aluminum product is adjusted. On the one hand, it can play a pinning role, and on the other hand, it can effectively refine the grains of the aluminum alloy and promote the formation of more crystal nuclei, thereby reducing the grain size, hindering dislocation movement, and significantly improving the strength of the aluminum product. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] In the following examples and comparative examples: Aluminum-copper alloy: copper content 50wt%, aluminum-manganese alloy: manganese content 20wt%, aluminum-chromium alloy: chromium content 5wt%, aluminum-titanium alloy: titanium content 5wt%; Single-walled carbon nanotubes: length 1~5μm, diameter 2~10nm, manufacturer is Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; Multi-walled carbon nanotubes: length 10~30μm, diameter 10~20nm, manufacturer is Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; Graphene: fineness is 1~3nm; Fullerene: Model is fullerene C70; Lanthanum oxide: average particle size 40nm; Cerium oxide: average particle size 50nm; Dysprosium oxide: average particle size 40nm.
[0019] Example 1 High-strength aluminum product, wherein the aluminum matrix is composed of the following components by weight percentage: Mg 3%, Cu 2%, Mn 0.5%, Zn 1.5%, Cr 0.01%, Ti 0.005%, and the balance is Al and inevitable impurities; A method for preparing a high-strength aluminum product comprises the following steps: S1. Mix magnesium ingots, aluminum-copper alloy (copper content 50wt%), aluminum-manganese alloy (manganese content 20wt%), zinc ingots, aluminum-chromium alloy (chromium content 5wt%), and aluminum-titanium alloy (titanium content 5wt%) according to target composition, heat to 700°C for rough refining to obtain rough-refined aluminum liquid, add magnesium silicate (the amount added is 0.5% of the mass of the rough-refined aluminum liquid) to the rough-refined aluminum liquid, refine, heat to 750°C, degas and deslag for 25 minutes, and obtain aluminum alloy melt; S2. Add a reinforcing phase (the amount added is 0.1% of the weight of the aluminum alloy melt) to the aluminum alloy melt, disperse it evenly, and die-cast it to obtain an aluminum product, wherein the reinforcing phase includes lanthanum oxide and graphene in a weight ratio of 1:1.
[0020] Example 2 High-strength aluminum product, wherein the aluminum matrix is composed of the following components by weight percentage: Mg 4%, Cu 3%, Mn 1%, Zn2%, Cr 0.02%, Ti 0.01%, and the balance is Al and inevitable impurities; A method for preparing a high-strength aluminum product comprises the following steps: S1. Mix magnesium ingots, aluminum-copper alloy (copper content 50wt%), aluminum-manganese alloy (manganese content 20wt%), zinc ingots, aluminum-chromium alloy (chromium content 5wt%), and aluminum-titanium alloy (titanium content 5wt%) according to target composition, heat to 725°C for rough refining to obtain rough-refined aluminum liquid, add aluminum silicate to the rough-refined aluminum liquid (the amount added is 0.75% of the mass of the rough-refined aluminum liquid), refine, heat to 775°C, degas and deslag for 20 minutes, and obtain aluminum alloy melt; S2. Add a reinforcing phase (the amount added is 0.1% by weight of the aluminum alloy melt) to the aluminum alloy melt, disperse it evenly, and die-cast it to obtain an aluminum product, wherein the reinforcing phase includes cerium oxide and single-walled carbon nanotubes in a weight ratio of 1:1.
[0021] Example 3 High-strength aluminum product, wherein the aluminum matrix is composed of the following components by weight percentage: Mg 5%, Cu 4%, Mn 1.5%, Zn 2.5%, Cr 0.03%, Ti 0.015%, and the balance is Al and inevitable impurities; A method for preparing a high-strength aluminum product comprises the following steps: S1. Mix magnesium ingots, aluminum-copper alloy (copper content 50wt%), aluminum-manganese alloy (manganese content 20wt%), zinc ingots, aluminum-chromium alloy (chromium content 5wt%), and aluminum-titanium alloy (titanium content 5wt%) according to target composition, heat to 750°C for rough refining to obtain rough-refined aluminum liquid, add calcium silicate to the rough-refined aluminum liquid (the amount added is 1% of the mass of the rough-refined aluminum liquid), refine, heat to 800°C, degas and deslag for 15 minutes, and obtain aluminum alloy melt; S2. Add a reinforcing phase (the amount added is 0.1% of the weight of the aluminum alloy melt) to the aluminum alloy melt, disperse it evenly, and die-cast it to obtain an aluminum product, wherein the reinforcing phase includes dysprosium oxide and fullerene in a weight ratio of 1:1.
[0022] Example 4 Compared with Example 2, the difference of Example 4 is that the amount of reinforcement phase added is 0.2% of the weight of the aluminum alloy melt.
[0023] Example 5 Compared with Example 4, Example 5 is different in that the single-walled carbon nanotubes are replaced with an equal amount of multi-walled carbon nanotubes.
[0024] Example 6 Compared with Example 4, Example 6 is different in that the single-walled carbon nanotubes are replaced with equal amounts of single-walled carbon nanotubes and multi-walled carbon nanotubes in a weight ratio of 1:1.
[0025] Example 7 Compared with Example 4, Example 7 is different in that the single-walled carbon nanotubes are replaced with equal amounts of single-walled carbon nanotubes and multi-walled carbon nanotubes in a weight ratio of 3:1.
[0026] Example 8 Compared with Example 4, Example 8 is different in that the single-walled carbon nanotubes are replaced with equal amounts of single-walled carbon nanotubes and multi-walled carbon nanotubes in a weight ratio of 4:1.
[0027] Example 9 Compared with Example 4, Example 9 is different in that the single-walled carbon nanotubes are replaced with equal amounts of single-walled carbon nanotubes and multi-walled carbon nanotubes in a weight ratio of 5:1.
[0028] Comparative Example 1 Compared with Example 2, the difference in Comparative Example 1 is that the amount of reinforcement phase added is 0.05% by weight of the aluminum alloy melt.
[0029] Comparative Example 2 Compared with Example 2, the difference of Comparative Example 2 is that the amount of reinforcement phase added is 0.25% of the weight of the aluminum alloy melt.
[0030] Comparative Example 3 Compared with Example 2, Comparative Example 3 is different in that no reinforcing phase is added.
[0031] Comparative Example 4 Compared with Example 2, Comparative Example 4 is different in that the reinforcement phase includes only cerium oxide.
[0032] Comparative Example 5 Compared with Example 2, Comparative Example 5 is different in that the reinforcement phase only includes single-walled carbon nanotubes.
[0033] The high-strength aluminum products obtained in Examples 1 to 9 and Comparative Examples 1 to 5 were tested according to the following method: Tensile strength: According to the test method for tensile strength specified in GB / T 228.1-2021 "Tensile test for metallic materials Part 1: Test method at room temperature", the tensile strength of the sample is tested. 2. Yield strength: According to the test method for yield strength specified in GB / T 228.1-2021 "Tensile test for metallic materials Part 1: Test method at room temperature", the yield strength of the sample is tested.
[0034] The test results are shown in the following table: Table 1 Performance test results of high-strength aluminum products obtained in Examples 1 to 9 and Comparative Examples 1 to 5
[0035] Compared with Example 2, Comparative Examples 1, 2 and Example 4 added different weights of reinforcing phases, and the tensile strength and yield strength of Examples 2 and 4 were better than those of Comparative Examples 1 and 2, indicating that when the weight ratio of the reinforcing phase to the aluminum product is 1 to 2:1000, the strength of the obtained aluminum product is higher. Compared with Example 2, Comparative Example 3 did not add a reinforcing phase composed of cerium oxide and single-walled carbon nanotubes, and the tensile strength and yield strength of Example 2 were better than those of Comparative Example 3, indicating that the addition of the reinforcing phase can improve the strength of the aluminum product; Compared with Example 2, Comparative Example 4 only added cerium oxide as a reinforcing phase, and Comparative Example 5 only added single-walled carbon nanotubes as a reinforcing phase, and the tensile strength and yield strength of Example 2 were better than those of Comparative Examples 4 and 5, indicating that cerium oxide and single-walled carbon nanotubes play a synergistic role, which can improve the tensile strength and yield strength of aluminum products and enhance the strength of aluminum products.
[0036] Compared with Examples 4 and 5, Examples 6 to 9 simultaneously added single-walled carbon nanotubes and multi-walled carbon nanotubes. As a result, the tensile strength and yield strength of Examples 6 to 9 were better than those of Examples 4 and 5, indicating that the single-walled carbon nanotubes and multi-walled carbon nanotubes play a synergistic role and can improve the strength of aluminum products. In Examples 6 to 9, single-walled carbon nanotubes and multi-walled carbon nanotubes were added in different weight ratios. As a result, the tensile strength and yield strength of Examples 7 and 8 were better than those of Examples 6 and 9, indicating that when the weight ratio of single-walled carbon nanotubes to multi-walled carbon nanotubes is 3 to 4:1, the strength of the obtained aluminum product is better.
[0037] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength aluminum product, characterized in that: The invention is composed of an aluminum matrix and a reinforcement phase. In terms of weight percentage, the aluminum matrix is composed of the following components: Mg 3%-5%, Cu 2%-4%, Mn 0.5%-1.5%, Zn 1.5%-2.5%, Cr 0.01%-0.03%, Ti 0.005%-0.015%, and the balance is Al and inevitable impurities; the reinforcement phase comprises rare earth oxides and carbon nanomaterials; the weight ratio of the reinforcement phase to the aluminum product is 1-2:1000; the weight ratio of the rare earth oxides to the carbon nanomaterials is 1:
1.
2. A high-strength aluminum product according to claim 1, characterized in that: The rare earth oxide includes one or more of lanthanum oxide, cerium oxide, and dysprosium oxide.
3. A high-strength aluminum product according to claim 1, characterized in that: The carbon nanomaterial includes one or more of carbon nanotubes, graphene, and fullerene.
4. A high-strength aluminum product according to claim 3, characterized in that: When the reinforcing phase is carbon nanotubes, the carbon nanotubes are composed of single-walled carbon nanotubes and multi-walled carbon nanotubes.
5. A high-strength aluminum product according to claim 4, characterized in that: The weight ratio of the single-walled carbon nanotubes to the multi-walled carbon nanotubes is 3-4:
1.
6. The method for preparing a high-strength aluminum product according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, preparing materials according to the components of the aluminum matrix, performing rough refining to obtain rough-refined aluminum liquid, adding a refining and slag-removing agent to the rough-refined aluminum liquid, refining, degassing and deslagging, and obtaining an aluminum alloy melt; S2. Adding a reinforcing phase to the aluminum alloy melt, dispersing the phase evenly, and die-casting to obtain an aluminum product.
7. The method for preparing a high-strength aluminum product according to claim 6, characterized in that: The refining slag cleaning agent is one or more of magnesium silicate, aluminum silicate and calcium silicate.
8. The method for preparing a high-strength aluminum product according to claim 6, characterized in that: The rough refining temperature is 700-750°C.
9. The method for preparing a high-strength aluminum product according to claim 6, characterized in that: The degassing and deslagging process is performed at a temperature of 750-800°C and for a time of 15-25 minutes.
10. The method for preparing a high-strength aluminum product according to claim 6, characterized in that: The amount of the refining slag cleaning agent added is 0.5% to 1% of the mass of the aluminum liquid after the rough refining.
Citation Information
Patent Citations
Carbonyl group coordination compound transmutative high-performance aluminum alloy material and manufacture method thereof
CN103131915A
Heat treatable aluminum alloys having magnesium and zinc and methods for producing the same
CN110241335A
Process for manufacturing thin sheets made of 7xxx aluminum alloy suitable for shaping and assembly
CN112424387A
Aluminum alloy brazing sheet and production method therefor
CN112955281A
7xxx wrought products with improved compromise of tensile and toughness properties and method for producing
EP4386097A1